The Penyuluhan Perilaku Hidup Bersih dan Sehat di SDN 02 Telemung, Banyuwangi - Prasasti, Azmi; Prayudeni, Sari; Kustriyani, Anung; Deviani, Dita Amanda; Gymnastiar, Farhan; Maulidia, Maulidia (Universitas Muhammadiyah Klaten, 2024)
The purpose of this community service is to improve the understanding and application of clean and healthy living behavior (PHBS) among students of SDN 02 Telemung, through socialization and education by lecturers and students of D3 Pharmacy STIKES Banyuwangi. The methods used in this service include initial observation, socialization and education, implementation and evaluation. Initial observations were made to determine the condition of students' understanding of PHBS. Socialization and education are carried out with the aim of providing clear and interesting information about the importance of personal hygiene, environmental sanitation, and healthy lifestyles. Implementation was carried out by direct application of clean and healthy living habits at school, followed by evaluation using pre and post tests to measure changes in student understanding. The results of the activity showed high enthusiasm from students in participating in socialization and education. The pre and post-test evaluation showed a significant increase in understanding, with an average pre-test score of 45 and post-test score of 85. This shows that this activity has succeeded in increasing students' awareness and knowledge of the importance of PHBS